Comparison of Antidepressant‐Like and Abuse‐Related Effects of Phencyclidine in Rats. Issue 8 (15th October 2014) - Hillhouse, Todd M.; Porter, Joseph H.; Negus, S. Stevens
Abstract <table-wrap position="anchor" orientation="portrait"> Preclinical Research </table-wrap> N‐methyl‐D‐aspartate (NMDA) receptor antagonists, such as ketamine, have emerged as novel candidate treatments for major depressive disorder, but abuse potential of these agents is a concern. The NMDA antagonist phencyclidine has known abuse liability but undefined efficacy as an antidepressant. To further evaluate the relationship between antidepressant‐like and abuse‐related effects of NMDA antagonists, this study evaluated the effects of phencyclidine (1.0–10.0 mg/kg) in male Sprague‐Dawley rats responding under two procedures that have been used to assess antidepressant‐like effects (differential‐reinforcement‐of‐low‐rate [DRL] 72 s schedule of food reinforcement; n = 9) and abuse‐related drug effects (intracranial self‐stimulation [ICSS]; n = 6). Under the DRL 72 s schedule, phencyclidine (10.0 mg/kg) increased reinforcers and decreased responses without shifting the peak location of the interresponse time (IRT) distribution. Ketamine (10.0 mg/kg) also increased reinforcers and decreased responses, but unlike phencyclidine, it produced a rightward shift in the peak location of the IRT distribution. The 10.0 mg/kg phencyclidine dose that decreased DRL 72 s responding also decreased rates of ICSS for 50 min after its administration; however, abuse‐related ICSS facilitation was observed at later times (100–300 min) or after a lower phencyclidine dose (3.2 mg/kg). These results suggest that phencyclidine produces weaker antidepressant‐like effects, but stronger abuse‐related effects than ketamine in these procedures.